PENERAPAN MODEL KOOPERATIF TIPE GROUP INVESTIGATION (GI) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD YKPP SUNGAI PAKNING - Khamsiati, Khamsiati; Lazim N, Lazim N; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The problem of this research is the weakness of student’s result learning of natural science subject fifth class students SD YKPP SUNGAI PAKNING, which is consist of 26 student’s. The KKM in this school is 75. From the total only 9 student’s ( 34,62%) reach the KKM and 17 student’s (65,38%) under the KKM. Based on the problem the reseacher doing the reseach implementation cooperative learning model investigation (GI). In cycle I, percentage of teacher activity in the first meeting is adquate (50,00%) in the second meeting teacher activity signivicantly increase up to (62,5%) with good category. In cycle II the first meeting was in very good category (83,33%) and the second meeting indecated a very good category (95,83%). Mean while the activity of student’s also improved. In cycle I, for the first meeting indicated (54,16%) in adquate category and the second meeting was increased up to (62,5%) with good category. In cycle II at the first meeting, the students activity has been increasing up to (79,16%) with good category and the second meeting increased up to (91,66%) with very good category. An average score of student’s result learning before implementation is (69,92). It increased up to (82,30) in cycle I and (89,03) in cycle II. In classical completeness, cycle I and cycle II were achieved. In conclusion the implementation cooperative learning model investigation (GI) can improve student’s result learning of fifth class student’s YKPP Sungai Pakning in natural subject.Key words: Method of Mind Maps (Group Investigation), learning outcomes IPA